Rottlerin Derivatives and Other Compounds from Mallotus philippinensis Fruits and Their Potential Antimycobactrial Activity - Bharadwaj, Rima; Chinchansure, Ashish A.; Kulkarni, Roshan R.; Arkile, Manisha; Sarkar, Dhiman; Joshi, Swati P. (Planta Medica Letters, 2015)
The methanolic extract of the fruits of Mallotus philippinensis afforded 13 compounds, 7,11-diketo-lanost-3-ol (1, as acetate), lanosta-8-ene-3β-ol (2, as acetate), pregnenolone (3, as acetate), trans-chalcone (4), kamalachalcone E (5), oleanolic acid (6), gallic acid (7), kaempferol (8), myricetin (9), 1-(5,7-dihydroxy-2,2,6-trimethyl-2 H-1-benzopyran-8-yl)-3-phenyl-2-propen-1-one (10), 4′-hydroxyisorottlerin (11), rottlerin (12), and shikimic acid (13). Compound 1 was isolated as a new natural product and its structure was elucidated by 1D and 2D nuclear magnetic resonance analyses including heteronuclear single quantum correlation, heteronuclear multiple-bond correlation, correlation spectroscopy, and nuclear Overhauser effect spectroscopy experiments. All of the isolated compounds were evaluated for their antimycobacterium activity against Mycobacterium tuberculosis H37Ra. Compounds 11 and 12 exhibited promising inhibitory activity with IC50 values of 0.89 ± 0.33 µg/mL (MIC 2.06 ± 0.41 µg/mL) and 7.59 ± 0.42 µg/mL (MIC 11.56 ± 0.35 µg/mL), respectively.
Keywords: Mallotus philippinensis; Euphorbiaceae; antimycobacterium; rottlerins; lanostanol; flavonoids